European Perspectives for Public Administration The Way Forward - Bouckaert, Geert; Jann, Werner (Leuven University Press, 2020)
"The public sector in our society has over the past two decades undergone substantial changes, as has the academic field studying Public Administration (PA). In the next twenty years major shifts are further expected to occur in the way futures are anticipated and different cultures are integrated. Practice will be handled in a relevant way, and more disciplines will be engaging in the field of Public Administration. The prominent scholars contributing to this book put forward research strategies and focus on priorities in the field of Public Administration. The volume will also give guidance on how to redesign teaching programmes in the field. This book will provide useful insights to compare and contrast European PA with PA in Europe, and with developments in other parts of the world."